Analysis of the Influence of Motivation Theory in the Implementation of Occupational Safety and Health at Manufacturing Companies to Improve Employee Compliance - Juan Ikhram Harvandhy; Fauzi Fahmi Achmad; Muhamad Hanif Giarsyah; Vito Dimas Mulyadi; Henny (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
Occupational safety and health or often referred to as OSH is the main pillar for the manufacturing industry to maintain employee welfare and productivity. This study analyzes the influence of motivation theory, specifically Maslow's needs theory, in improving workers' compliance with OSH implementation in Manufacture Company. The study employed a quantitative methodology approach through a data collection method involving 30 respondents from Manufacture Company. A Likert scale-based questionnaire was used to gather the data and SPSS 26 was used for analysis with validity, reliability, normality, and factor analysis tests. The results showed that five elements of motivation - physiological, safety, social, esteem, and self-actualization needs - had a significant influence on workers' compliance with OSH with the social needs element having the greatest influence. Thus, Maslow's needs theory is proven to have an influence in improving employee compliance with OSH implementation in industry.